A Report on Harry Stottlemeier - Gunter, Cynthia (Analytic Teaching, 2014)
Introduction:  "It is a mistake to think that we can engage children in the educational process without engaging them in reflection about what they are doing" (Lipman, 1979, p. 128).  According to Lipman, we cannot expect children to want to be actively involved in their own education unless we encourage and provide the opportunity for them to reflect on what it is that they are doing when they are doing it.  Meaning it is not something that can be dispensed or force-fed, children must seek it out and discover it for themselves.  Analytic Teaching, by promoting inquiry through discussion, is a way by which children can become actively involved in seeking meaning and reflecting on what their education is all about.